Ethnobotanical appraisal and in-silico investigation of plants used for the management of COVID-19 in Southwestern Nigeria (2021)
The continued spread of 2019 novel coronavirus disease is a serious threat to global health. Currently, no approved vaccines or antiviral agents for treatment exist, but, there are many anecdotal accounts of the use of herbal concoctions for the management of this disease in many low-income settings, including Nigeria abound. Using a combination of a web-based survey, and face-to-face interviews with local herbal sellers, this study documents the herbal flora used in the management of COVID-19 in Southwestern Nigeria, and also probes their potential as inhibitors of SARS-CoV-2 proteins. The preliminary in-silico studies identified taraxerol, vernonioside D2, nimbolide and mangiferoleanone as potential hit candidates for COVID-19. The current findings highlight that nature can be a source for the discovery of medicinal agents active against COVID-19. These preliminary results necessitate further in-vitro and in-vivo experimental evidence.